Fission Yeast CSL Transcription Factors: Mapping Their Target Genes and Biological Roles. - Martin Převorovský; Martina Oravcová; Jarmila Tvarůžková; Róbert Zach; Petr Folk; František Půta; Jürg Bähler (PLoS ONE)
Background Cbf11 and Cbf12, the fission yeast CSL transcription factors, have been implicated in the regulation of cell-cycle progression, but no specific roles have been described and their target genes have been only partially mapped. Methodology/principal findings Using a combination of transcriptome profiling under various conditions and genome-wide analysis of CSL-DNA interactions, we identify genes regulated directly and indirectly by CSL proteins in fission yeast. We show that the expression of stress-response genes and genes that are expressed periodically during the cell cycle is deregulated upon genetic manipulation of cbf11 and/or cbf12. Accordingly, the coordination of mitosis and cytokinesis is perturbed in cells with genetically manipulated CSL protein levels, together with other specific defects in cell-cycle progression. Cbf11 activity is nutrient-dependent and Δcbf11-associated defects are mitigated by inactivation of the protein kinase A (Pka1) and stress-activated MAP kinase (Sty1p38) pathways. Furthermore, Cbf11 directly regulates a set of lipid metabolism genes and Δcbf11 cells feature a stark decrease in the number of storage lipid droplets. Conclusions/significance Our results provide a framework for a more detailed understanding of the role of CSL proteins in the regulation of cell-cycle progression in fission yeast.